Study on immersion corrosion behavior and mechanism of SDCM die steel for hot stamping. (July 2022) - Jiang, Bin; Zuo, Pengpeng; Wu, Xiaochun
Highlights: In this paper, the corrosion of hot stamping water channel was studied systematically. The experiment was carried out by immersing in deionized water. The corrosion behavior and mechanism were studied by using different stress, hardness and different heat treatment process. Obtained 3 kinds of hardness, applied stress from 50MPa to 700MPa, got different corrosion morphologies. Used corrosion area and pitting aspect ratio to measure corrosion degree. Analyzed corrosion mechanism from microstructure and carbide type distribution. The pitting formation model of Cr-Mo-V alloys was discussed. Abstract: Adopted immersion method to systematically study the corrosion behavior of SDCM steel for hot stamping. For specimens with the same hardness of 54 HRC, the corrosion resistance of 1030 °C quenched samples were better than that of 1060 °C quenched samples. After 1030 °C quenched, the hardness was adjusted to 50 HRC, 52 HRC and 54 HRC by tempering process, and then applied 50 MPa tensile stress to these three kinds of hardness samples. With the increase of hardness, the corrosion area decreased from 21.82% to 13.47%, and the number of large pits decreased from 27 to 7 on the area of 40 mm 2 . Stress has an important effect on corrosion. When the loading stress was less than 100 MPa, the corrosion area/pitting numbers increased with the increase of stress, but the aspect ratio decreased, and the decreasing range was large. When the loading stress was more than 100 MPa, the corrosion area/pitting number decreased with the increase of stress, the aspect ratio also decreased, but the decreasing range was smooth, which was mainly related to the concentration of adsorbed dissolved oxygen; finally, we discussed the initiation and growth behavior of pitting pits and then schematically described its model.